The Effect of Radiation on the Gut Bacteriome of Aedes albopictus - Zhang, Dongjing; Chen, Shi; Abd-Alla, Adly M. M.; Bourtzis, Kostas (Frontiers in Microbiology, 2021)
The sterile insect technique (SIT) has been developed as a component of area-wide integrated pest management approaches to control the populations of Aedes albopictus, a mosquito vector capable of transmission of dengue, Zika and chikungunya viruses. One of the key factors for the success of SIT is the requirement of high biological quality sterile males, which upon their release would be able to compete with wild males for matings with wild females in the field. In insects, gut bacteriome have played a catalytic role during evolution significantly affecting several aspects of their biology and ecology. Given the importance of gut-associated bacterial species for the overall ecological fitness and biological quality of their hosts, it is of interest to understand the effects of radiation on the gut-associated bacteriome of Ae. albopictus. In this study, the effect of radiation on the composition and density levels of the gut-associated bacterial species at the pupal stage as well as at 1-day-old and 4-day-old males and females was studied using 16S rRNA gene-based next generation sequencing (NGS) and quantitative PCR (qPCR) approaches. Age, diet, sex, and radiation were shown to affect the gut-associated bacterial communities, with age having the highest impact triggering significant changes on bacterial diversity and clustering among pupae, 1-day-old and 4-day-old adult samples. qPCR analysis revealed that the relative density levels of Aeromonas are higher in male samples compared to all other samples and that the irradiation triggers an increase in the density levels of both Aeromonas and Elizabethkingia in the mosquito gut at specific stages. Our results suggest that Aeromonas could potentially be used as probiotics to enhance protandry and sex separation in support of SIT applications against Ae. albopictus, while the functional role of Elizabethkingia in respect to oxidative stress and damage in irradiated mosquitoes needs further investigation.